Leveraging Social Media as a Promotional Tool for Local Brands - Lestari Kamilasari, Dian; Satrio w, Gelar (Politeknik Negeri Madiun, 2024)
Social media serves as one of the digital marketing channels to promote a brand or product through platforms such as Instagram, WhatsApp, TikTok, YouTube, and Facebook. Papa Cookies Ponorogo utilizes social media, particularly Instagram and WhatsApp, as marketing tools to promote its products. Although the Instagram account does not upload content regularly every month, the business still records a significant number of purchases. The purpose of this study is to describe the utilization of Instagram and WhatsApp by Papa Cookies Ponorogo in digital marketing activities. This study uses a descriptive qualitative method with primary and secondary data sources. Data were collected through interviews, observation, and documentation involving three informants directly related to promotional activities. The collected data were systematically presented and analyzed descriptively. The results show that the utilization of social media at Papa Cookies Ponorogo includes four main indicators. In the context indicator, social media is used to share information through photo pamphlets and product videos. In the communication indicator, interaction is carried out by responding to customer inquiries through Instagram comments and WhatsApp private messages. In the collaboration indicator, cooperation is established with government institutions through the KIA (Kartu Indonesia Amanah) program. In the connection indicator, contact information and product catalogs are provided on Instagram and WhatsApp profiles. Thus, social media utilization proves effective in supporting promotional activities and strengthening customer relationships.